Egg production, nutrient utilization and metabolism in Lohmann LSL lite hens fed corn and soybean meal-based diet supplemented with multiple doses of single ß-mannanase from 63 to 83 weeks of age - Elijah G. Kiarie; Veronica Cheng; Felix M. Njeri; Reza Bakhshalinejad; Ahmed M. Amerah; Anna Fickler; Adebayo O. Sokale (Poultry Science)
The impact of supplementing multiple doses of single ß-mannanase (BM) in corn and soybean meal-based diets was investigated in Lohmann LSL lite hens. Corn and soybean meal-based diets were formulated to meet or exceed nutrient specifications and supplemented with BM at 0, 200, 400, 800 and 1,200 TMU/kg of feed. All diets contained titanium dioxide indigestible marker and were prepared in mash form. Three hundred and twenty hens at 63 weeks of age (woa) were placed in enriched cages (4 birds/cage). Diets were allocated to give 16 replicate cages/diet. Birds had free access to water and feed to 83 woa. Hen day egg production (HDEP), feed intake (FI), FCR, egg weight (EW), egg mass (EM), eggshell breaking strength (ESBS) and thickness (EST), Haugh unit (HU) and yolk color were reported at 4 weeks periods. Apparent retention (AR) of components and metabolizable energy (AME) were determined at 4th and 17th week of the experiment. Plasma metabolites, ceca digesta short chain fatty acids (SCFA), body and organ weight were determined at the end of the experiment. Interactions (P ≤ 0.05) between BM and period/sampling time point was observed for HDEP, EW, EM, FCR and AR of neutral detergent fiber (ARNDF) such that there were period dependent linear and non-linear responses to BM. Independent of the period, BM increased HDEP (P = 0.025, cubically), EW (P ≤ 0.018, linearly and quartically), EM (P < 0.01, quartically). The FCR reduced linearly (P = 0.032) in response to BM. Birds receiving BM800 had higher ARNDF than birds receiving BM0 at 4th wk sampling. The ESBS increased (P = 0.040, cubically) whereas HU decreased (P = 0.048, quadratically) in response to BM. The AR of DM, CP and AME, plasma glucose, cholesterol, lactate dehydrogenase, lipase Ca, P, and abdominal fat increased (P < 0.05) linearly in response to BM. There were no BM effects (P > 0.05) on SCFA. In conclusion, BM improved HDEP; egg quality and nutrient retention dose dependently. Moreover, plasma metabolites indicated positive effects on indices of carbohydrate and lipid metabolism.